Influence of Plasma Lipoproteins on the Fibrinolytic Activity - Skrzydlewski, Z; Niewiarowski, S (Thrombosis and Haemostasis, 1967)
Native lipoprotein fractions : alpha, beta and chylomicrons have been isolated from human serum according to the method of Burstein. Alpha lipoproteins and chylomicrons do not inhibit plasmin. The antiplasmin activity of beta lipoprotein amounts to about 10% of the total plasma antiplasmin activity. It is inactivated during heating at 56° C for 10 min, while storing at 4° C for a few days and by chloroform treatment. About 50% of serum beta lipoprotein is precipitated in euglobulin fraction. Variations of serum beta lipoprotein level have a significant effect on euglobulin fibrinolysis. Beta lipoprotein level, beta lipoprotein antiplasmin activity and euglobulin fibrinolysis have been determined in 2 groups of lipemic patients : a) puerperal women, b) patients with advanced atherosclerosis. There is a close correlation of beta lipoprotein level and euglobulin fibrinolysis time in puerperal patients. The inhibition of euglobulin fibrinolysis in patients with atherosclerosis depends on several factors, and only partly of the beta lipoprotein level. Beta lipoprotein level and beta lipoprotein antiplasmin activity were well correlated in both groups of patients.